Compliance forces, domestic policy process, and international regulatory standards: Compliance with Basel III. (March 2020) - Coban, Mehmet Kerem
Abstract: This article contributes to our understanding of how and why developing countries would comply with international banking regulatory standards, Basel standards. The article demonstrates the interplay between opportunity structures constituted by transnationalization of public policymaking and domestic institutional setting, and how forces of compliance resonate in the domestic politics of compliance. The empirical findings are based on Turkey's compliance with Basel standards. It relies on fieldwork that involves semi-structured qualitative interviews with senior regulators and bankers, which are complemented with analysis of secondary data. The article shows that a capable and willing regulator could capitalize on the top-down policymaking style which restricts the regulatee's access to international negotiations, and sets the terms at the domestic level. Direct access to international negotiations, resource asymmetry in favor of the regulator, and superior "negotiation knowledge" helped the regulator pacify a critical, skeptical regulatee, and drive the compliance process. The article also shows that the compliance process takes place at three stages: policy formulation at the international level, an "interpretation stage" in between the international and the domestic levels, and finally the domestic policy process.